The identity of Senecio topkegolensis (Asteraceae, Senecioneae) from Nepal - Tong, Tian-Jing; Ren, Chen; Yang, Qin-Er (Phytotaxa, 2017)
Critical examination of herbarium specimens (including type material) and living plants has shown that Senecio topkegolensis described from Nepal is conspecific with S. biligulatus, a species fairly common in the Himalayan region. We therefore place the former in synonymy with the latter.